The Expansion of Teenagers’ Slang Language Application Found in Batam - Suhardianto Suhardianto; Ambalegin Ambalegin (Universitas Lancang Kuning, 2017)
This research is a development of previous research conducted by researchers such as theconstruction of the formation of slang language, the form of slang greetings and adolescent perspective in its usefound in Batam. In the present study, the researchers again conducted a follow-up study of slang in order to findthe spread of adolescent slang use, the social aspects that influenced the use of slang, and the group of slangtypes in the adolescent community. This research is descriptive qualitative research because researchers use datain the form of words instead of numbers taken from the main source and interpreted by instinct and theresearcher's understanding of this research object. In data collection, the researcher will use the methodcompiled by Sudaryanto [1]. At the stage of providing data of researchers using the metode simak with SimakBebas Libat Cakap Technique. At this stage the researcher performs a silent observation and recording the useof slang in teen community. Recorded data will be transcribed in phonemic form and interpreted by the author.At the stage of data analysis the researchers used the Padan Method with basic techniques of Piliah UnsurPenentu (PUP) with pragmatic form. The results of the analysis aim to find out the rules about extending the useof slang in adolescent communities, social aspects that influence the use of slang, and grouping the types ofslang in teenagers in Batam. From the analysis of data collected, it can be found that the expansion of slang usein adolescent community occurs in all aspects of the use of language either written or oral form. In written formcan be found in social media and writing such as facebook, instagram, WA, Twitter, BBM, Path, paper, andLine. In the oral form it is contained in live conversations in a secretly recorded teenage community and also inthe film.